1993
DOI: 10.1139/b93-110
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and contrasting habitat colonization in Festuca pallescens

Abstract: Eight populations of Festuca pallescens (Poaceae) from southern Patagonia (Argentina) were chosen to test whether their morphology and anatomy were associated with climatic and edaphic characteristics of their habitats and to discriminate genetic and plastic components of the variation. Fourteen environmental variables were measured to characterize eight localities. Cluster analysis classified them into four habitats. Principal components analysis based on 22 morphological and anatomical characters of five ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Indeed, it has long been hypothesized that the success of widespread weed species is due to the great adaptive plasticity of their individuals, which allows them to colonize a variety of habitats successfully (Baker 1965, 1974; Bazzaz 1986) and hence wide geographical ranges as well (Rabinowitz 1981). The results of several recent studies support this hypothesis (Oliva et al . 1993; Williams et al .…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, it has long been hypothesized that the success of widespread weed species is due to the great adaptive plasticity of their individuals, which allows them to colonize a variety of habitats successfully (Baker 1965, 1974; Bazzaz 1986) and hence wide geographical ranges as well (Rabinowitz 1981). The results of several recent studies support this hypothesis (Oliva et al . 1993; Williams et al .…”
Section: Discussionsupporting
confidence: 55%
“…Austin & Sala (2002) showed that leaf N content increased with precipitation across an even wider range of moisture. In a study of phenotypic variation, Oliva et al (1993) found that Festuca pallescens growing in dry areas of Patagonia had shorter, tougher leaves than plants growing in more humid environments. At least in Patagonia, aridity appears to favour grazing-avoidance traits, while tolerance traits, such as higher leaf N, increase with precipitation.…”
Section:          mentioning
confidence: 99%
“…These results support the view that similar, functionally plastic populations may successfully occupy diverse sites in generalist species. This indicates that highly plastic species may consist of adaptively similar, generalist populations in diverse field habitats rather than narrowly specialized ecotypes (Oliva et al 1993;Williams et al 1995).…”
Section: Population Differentiation and Plasticitymentioning
confidence: 99%
“…Generalist plant species inhabit a wide range of habitats, including resource-poor and variable sites and may therefore be geographically widespread (Bazzaz 1986;Oliva et al 1993). This ecological breadth can reflect individual phenotypic plasticity, genetic differentiation of populations to local environmental conditions, or a combination of both aspects of variation (Bradshaw 1965;Van Tienderen 1990;Rice and Mack 1991;Emery et al 1994).…”
Section: Introductionmentioning
confidence: 99%